A influência do turnover de funcionários no desempenho empresarial - Pereira, Amanda Thaíse Galdino da Silva (Universidade Federal Rural do Semi-Árido, 2017)
With the advent of globalization, human capital flourished in the global economy. Organizations have become more flexible and have come to regard knowledge and professional experience as indispensable variables in decision making. In the same way, employees are characterized as collaborators capable of promoting the economic development of organizations. Through this perspective, it is necessary to recognize the possible impacts caused by the turnover index, that is, the turnover of employees in an organization. In this context, the objective of this study was to analyze whether employee turnover influences the corporate performance of the companies listed on BM & FBovespa. The methodology used consisted of hypothesis testing for this variable and the value of the coefficient β₁ will indicate if the turnover influences the performance and whether this influence is positive or negative. All companies listed on the BM & FBovespa were analyzed and, from this population, all companies that did not have data for some variable included in the econometric model and all financial companies were excluded. At the end of the filtering, 184 non-financial firms made up 921 observations over the period from 2010 to 2015. The main results suggest that firm size influences business performance by analyzing through return on assets and on The shareholders' equity. It was also verified that the state or more indebted companies have lower corporate performance than the others. In this perspective, the contributions of this study to the national literature are highlighted, since this theme in national studies is under development.
Artigo
Keywords: Rotatividade de funcionários; Desempenho empresarial; Lucratividade; Turnover of employees; Business Performance; Profitability; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO